MEDIATING EFFECTS OF PSYCHOLOGICAL CAPITAL AND BURNOUT SYNDROME ON THE RELATIONSHIP BETWEEN BUDGETARY PARTICIPATION AND MANAGEMENT PERFORMANCE - Schlup, Daiani; Beck, Franciele; Zonatto, Vinícius Costa da Silva (Advances in Scientific and Applied Accounting, 2021)
Objective: This study aimed to evaluate the mediating effects of Psychological Capital and Burnout Syndrome in the relationship between Budget Participation and Management Performance. Method: A descriptive survey was developed, with a quantitative approach to the data. The sample analyzed corresponds to 203 managers with budgetary responsibility for the largest companies in Brazil, occupying positions of controllers, controllership managers and cost managers. Data analysis was performed using descriptive statistics, factor analysis, structural equation modeling, as well as additional analysis using linear regression. Results: The results show that in environments with greater budgetary participation, individuals tend to develop their psychological capital better, becoming more optimistic, hopeful, resilient and self-effective, mitigating the negative effects of the burnout syndrome and, consequently, leveraging their management performance. As for the comparison of responses of managers who held controllership or cost positions, the only significant difference was the burnout syndrome, which may indicate that controllers tend to be more flexible when faced with a failure in budget control and may suffer less from the negative effects of the work environment, that generate tensions that can result in burnout syndrome. Contributions: As a general contribution, demonstrating the influence of budgetary participation on the cognitions and performance of individuals in organizations, as well as the informational roles of the budget and the influence of the budgetary configuration adopted by companies on human behavior at work.